The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/polym14132625
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure Analysis of Drawing Effect and Mechanical Properties of Polyacrylonitrile Precursor Fiber According to Molecular Weight

Abstract: Polyacrylonitrile (PAN) fiber is the most widely used carbon fiber precursor, and methyl acrylate (MA) copolymer is widely used for research and commercial purposes. The properties of P (AN-MA) fibers improve increasingly as the molecular weight increases, but high-molecular-weight materials have some limitations with respect to the manufacturing process. In this study, P (AN-MA) precursor fibers of different molecular weights were prepared and analyzed to identify an efficient carbon fiber precursor manufactu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 31 publications
(48 reference statements)
0
2
0
Order By: Relevance
“…XRD showed that the electrospun nanofibers contained crystals ( Figure 2 ). The solvent medium, parameters, applied voltage, and polymer characteristics (molecular weight) all affect the crystal structure [ 33 ]. XRD was taken to analyze the modifications in the crystalline structure of the pristine electrospun PCL/CH/CMF nanofiber membrane.…”
Section: Resultsmentioning
confidence: 99%
“…XRD showed that the electrospun nanofibers contained crystals ( Figure 2 ). The solvent medium, parameters, applied voltage, and polymer characteristics (molecular weight) all affect the crystal structure [ 33 ]. XRD was taken to analyze the modifications in the crystalline structure of the pristine electrospun PCL/CH/CMF nanofiber membrane.…”
Section: Resultsmentioning
confidence: 99%
“…Electrospinning is a convenient and efficient technique to immobilize a catalyst onto polymer fiber [ 26 , 27 , 28 , 29 , 30 ], and the supported particles would be adhesively fixed onto the surface of the nanofibers during the fibers’ formation process, or bonded onto active groups of polymers by coordination [ 31 , 32 ], a hydrogen bridge [ 33 ], a covalent bond [ 34 , 35 ], etc. In addition, polyacrylonitrile has excellent mechanical properties, chemical tolerance, and high affinity to organic pollutants, especially its light resistance ability, which makes it a great potential polymer support for a photo-enhanced catalyst [ 36 , 37 ]. In our previous study, iron phthalocyanine (FePc) particles were immobilized onto the surface of PAN yarns through the fifth ligand coordination between hydroxyl groups from modified PAN and Fe atoms from FePc, which showed stable and efficient catalysis in degrading dyes [ 38 , 39 , 40 ].…”
Section: Introductionmentioning
confidence: 99%